Chile : Trade Performance, Trade Liberalization, and Competitiveness - Monfort, Brieuc (IMF Working Papers; Working Paper ;, 2008)
This paper analyses the evolution of Chile's trade between 1990 and 2007, studying in particular the impact of trade liberalization in addition to traditional price and demand determinants. The results show that export and import flows are mainly responsive to external and domestic demand, and less so to relative prices, although there is a small impact on imports. In addition, the analysis suggests that trade liberalization may have played a role in increasing exports and imports. Estimations of trade elasticities for other countries in Latin America tend to confirm the results found for Chile.